Psychometric characteristics of the Spanish version of the HIV Symptom Index - Olatz Ibarra-Barrueta; Oihana Mora-Atorrasagasti; Itziar Palacios-Zabalza; Urko Aguirre-Larracoechea; Maria Jose Legarreta; Nerea González-Hernández (SpringerOpen, 2024)
Abstract Background The aim of this study was to determine the psychometric properties of the Spanish-language version of the HIV-Symptom Index (HIV-SI) questionnaire in Spanish patients undergoing antiretroviral therapy. Methods Between 2014 and 2016, an observational, multicenter, prospective cohort study was conducted in seventeen Spanish hospitals to validate HIV-SI questionnaire in terms of: construct validity (confirmatory factor analysis), internal consistency (Cronbach's alpha), convergent validity (Pearson's correlation coefficient) and Known-group validity. In addition, a sensitivity to change analysis was also performed. Results A total of 232 patients were included in the study. They had a mean age of 46.17 (SD9.82) and were 75% male. The median overall score for the HIV-SI was 10 (IQR 4- 19.5) and the most common symptoms reported were feelings of nervousness or anxiety, fatigue or energy loss, feeling sad or depressed, stomach pain or bloating, and difficulty sleeping. In the current study, the Spanish HIV-SI questionnaire showed a high internal consistency (α = 0.89) and adequate construct validity (CFI and TLI > 0.90). When contrasted with the MOS-HIV questionnaire, an inverse correlation was found. It showed a good association with the mental (r=-0.61; P < 0.0001) and physical score (r=-0.60; P < 0.0001). In a multivariate analysis, the age of the patient, female condition, hepatitis C coinfection, concomitant treatment and non-adherence resulted in a higher HIV-SI score. Conclusions Our study has shown that the Spanish HIV-SI is a valid and reliable self-administered PROM for routine measurement of patient- reported symptoms among Spanish patients on antiretroviral treatment.